Monitoring of Educational Institutions Information Resources in the Republic of Belarus as a Tool for Implementing Policies in the Field of Export of Educational Services - A. B. Belsky; A. V. Lipovich; A. P. Moskalenko, (Цифровая трансформация)
The article considers the issues of monitoring of the educational institutions official websites in the Republic of Belarus, beginning with the 2018 interms of its influence on the potential of services export in education. Special attention is paid to a state and development of information resources of higher education institutions. Regulatory legal acts and other documents forming a normative basis of monitoring are analyzed. The organization of monitoring processes of the education institutions websites is considered in the manual regime as well as using the  utomated information system for auditing education institutions information resources in the Republic of Belarus, assessment of their state and relevance is also considered (AIS Monitoring). The criteria for evaluation of the websites included in monitoring are presented and their comparison at the manual and automated way of realization is carried out. The analysis of monitoring results of the education institutions official websites in 2018 including that realized within trial operation of AIS Monitoring is produced. The correlation between the growth in the number of foreign students in higher education institutions and indicators for monitoring of information resources is assessed. The results of a quantitative assessment of the dependence of the growth rate of the number of foreign students at Belarusian universities on the level of compliance with the requirements for the informational content of official sites in terms of the list and cost of services provided in the form of a regression model are presented. Recommendations for further development and improvement of monitoring processes of information resources are formed.